Experimental and Theoretical Structure Elucidation of the [2 : 1] Complex Ion of Carbo[n]helicene with n=6, 7 and 8 and Ag+ - Oschwald, Johannes; Reger, David; Frühwald, Stefan; Warmbrunn, Vera; Görling, Andreas; Jux, Norbert; Drewello, Thomas (ChemPhysChem, 2023)
Gas-phase complexes of [n]helicenes with n=6, 7 and 8 and the silver(I) cation are generated utilizing electrospray ionization mass spectrometry (ESI-MS). Besides the well-established [1 : 1] helicene/Ag+-complex in which the helicene provides a tweezer-like surrounding for the Ag+, there is also a [2 : 1] complex formed. Density functional theory (DFT) calculations in conjunction with energy-resolved collision-induced dissociation (ER-CID) experiments reveal that the second helicene attaches via π-π stacking to the first helicene, which is part of the pre-formed [1 : 1] tweezer complex with Ag+. For polycyclic aromatic hydrocarbons (PAHs) of planar structure, the [2 : 1] complex with silver(I) is typically structured as an Ag+-bound dimer in which the Ag+ would bind to both PAHs as the central metal ion (PAH–Ag+–PAH). For helicenes, the Ag+-bound dimer is of similar thermochemical stability as the π-π stacked dimer, however, it is kinetically inaccessible. Coronene (Cor) is investigated in comparison to the helicenes as an essentially planar PAH. In analogy to the π-π stacked dimer of the helicenes, the Cor−Ag+−Cor−Cor complex is also observed. Competition experiments using [n]helicene mixtures reveal that the tweezer complexes of Ag+ are preferably formed with the larger helicenes, with n=6 being entirely ignored as the host for Ag+ in the presence of n=7 or 8.
CRIS-Team Scopus Importer:2023-09-15
Keywords: carbo[n]helicenes; density functional calculations; Energy-resolved CID; tweezer; [2 : 1] helicene/silver(I) complex ion